Diplomasi Iklim dan Keadilan: Tiga Pilar Indonesia-Jepang Dalam Asia Zero Emission Community - Zahra, May Fariza; Alfajri, Alfajri (UIR Press, 2026)
The Asia Zero Emission Community (AZEC) initiative is a multilateral platform launched by Japan to accelerate decarbonisation in Asia, including Indonesia. However, its implementation has drawn criticism from 41 civil society organisations, which argue that AZEC projects still rely on low-emission technologies that lack transformative potential and have not adequately integrated equity considerations. This study aims to analyse how Indonesia–Japan climate diplomacy can reshape AZEC to realise procedural and distributive justice, as well as accountability. This study employs a qualitative approach through a literature review using the framework of Neoliberal Institutionalism, alongside the concepts of International Regimes and Climate Justice. The analysis focuses on the interactions between state and non-state actors in the formulation and implementation of energy transition policies within the AZEC framework. The research findings indicate that the disregard for civil society aspirations triggers an erosion of the regime’s legitimacy and undermines the credibility of Indonesia–Japan climate diplomacy –Japan at the global level; consequently, the AZEC requires reconstruction through the integration of climate justice principles, the restructuring of inclusive decision-making mechanisms, the establishment of an independent oversight system, and the reorientation of funding towards community-based renewable energy to ensure the regime’s sustainability.